ELEMENTS OF ACCOUNTING POLICY SELECTION AND ITS INFLUENCE ON FINANCIAL STATEMENTS INDICATORS - O. Ageeva (Publishing House of the State University of Management, 2019)
In this article, the authors consider reasons for development of variety of accounting policies and examine influencing of selected accounting policy elements on valuation of financial statements indicators. Obviously financial statements indicators are definitely one of the most important sources of information for financial analysis and management decisions. Financial analyst should be aware, which valuation methods have been presented in this financial statement, and how they influence on formulated by him analytical conclusions. The approach presented in the article to the assessment of the impact of accounting policies on the financial statements’ indicators and the conclusions formulated by the authors as a result of the research allows to get answers to these issues.